Outcomes of Cases of Prenatally-Diagnosed Congenital Pulmonary Airway Malformation - Mehmet Sinan Beksac; Erdem Fadiloglu; Atakan Tanacan; Canan Unal; Neslihan Bayramoglu Tepe; Emine Aydın; Gokcen Orgul; Murat Yurdakok (Revista Brasileira de Ginecologia e Obstetrícia, 2019)
Abstract Objective To evaluate the outcomes of cases of prenatally-diagnosed congenital pulmonary airway malformation (CPAM). Methods We retrospectively evaluated cases of prenatally-diagnosed CPAM between 2004 and 2018. Ultrasonographic features such as visualization of a fetal lung mass and heterogeneous pulmonary parenchyma were used for CPAM diagnosis. Prenatal and postnatal findings were compared in terms of accuracy regarding the CPAM diagnosis. Results The sample consisted of 27 cases. There were four cases in which the patients opted for the termination of pregnancy due to the severity of the lesion. A total of 23 neonates were delivered, and CPAM was confirmed in 15 cases. Themedian gestational age at delivery was 37 weeks (28-40 weeks) and the mean birth weight was 2,776 g. There were two neonatal deaths, one due to pneumothorax, and the other due to hypoplastic left heart syndrome (HLHS). A total of five patients with respiratory problems were operated in the postpartum period. There were eight misdiagnosis: bronchopulmonary sequestration (five cases), congenital lobar emphysema (two cases), and congenital diaphragm hernia (one case). Conclusion A precise postnatal diagnosis is very important to organize the proper management of the pregnancies with fetuses with CPAM. The positive predictive value of the prenatal diagnosis of CPAM via ultrasonography is of 70.3%. The differential diagnosis of CPAM may be prolonged to the postpartum period in some cases.